Ethnobotanical study on wild edible plants used by Dulong people in northwestern Yunnan, China - Zhuo Cheng; Xiaoping Lu; Fengke Lin; Abid Naeem; Chunlin Long (BMC, 2022)
Abstract Background Dulong (Drung people) are one of the ethnic minorities of China, consisting of a small population living in remote and mountainous regions with limited facilities. Over the years, the Dulong have maintained their livelihood by collecting wild medicinal and edible plants. Therefore, through their experience and understanding, they had accumulated sufficient traditional knowledge about local plant resources. Since ancient times, wild edible plants have been essential to the food security of the Dulong people. However, there is almost no comprehensive report available on WEPs consumed by the Dulong people. The objectives of this study were to: (1) make a systematic study of WEPs used by Dulong people, (2) record traditional knowledge related to WEPs, (3) analyze multiple uses of WEPs, and (4) evaluate species with significant cultural significance to Dulong people. Methods Ethnobotanical survey including free listing, semi-structured interviews, key informant interviews and participatory observations was conducted in Dulongjiang Township, Gongshan County, Yunnan Province, Southwest China. A total of 127 informants were selected using the snowball method and information about WEPs, including vernacular name, food categories, parts used, mode of consumption, collection season, and other local uses were collected. The RFC and CFSI were calculated to identify the most culturally significant WEPs. One-way analysis of variance was performed to evaluate whether the four reference variables (gender, age, occupation, and education) significantly influenced the number of plant species mentioned by the respondents. Results and discussion A total of 148 species of WEPs consumed by the Dulong people belonging to 58 families were collected, including wild vegetables (71), wild fruits (52), staple food substitutes (15), spices (7), nuts (4), tea substitute (2), liquor making materials (3) oils and fats (3), and culinary coagulants (1). WEPs are used in a number of different ways, including as fuelwood, feed, and medicine. Food substitute plants accounted for the majority of the top 27 wild food plants identified by RFC and CFSI. It was observed that farmers have more knowledge of WEPs, and moderate education level informants reported less WEPs used. Conclusion The WEPs used by the Dulong people are diverse and abundant in the Dulongjiang region. In the future, WEPs such as Maianthemum atropurpureum, Caryota obtusa, Cardiocrinum giganteum, and Angiopteris esculenta with economic potential can be developed to provide a source of income for the residents. More studies of the nutritional value, chemical composition, and biological activities of WEPs are needed. The demands and development of local communities can be realized under the premise of protecting WEPs and the associated traditional knowledge. More attention should be paid to the value of WEP and underutilized plants during future rural development.